HUBUNGAN INTENSITAS MENONTON TAYANGAN KEKERASAN DI TELEVISI, REGULASI EMOSI DAN KELEKATAN AMAN TERHADAP KECENDERUNGAN KENAKALAN REMAJA - , Putri Mashita Asri; , Prof. Dr. Sofia Retnowati, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the relationship of the intensity of watching violence on television , emotion regulation , secure attachment with a tendency to juvenile delinquency . The hypothesis of this study is that there is a relationship between the intensity of watching violence on television , emotion regulation , secure attachment towards the tendency of juvenile delinquency . The subjects of this study are 115 students in High School at Klaten . Data was collected using a scale tendency of juvenile delinquency , the scale of the intensity of watching violence on television , the scale of emotion regulation and secure attachment scale . Techniques of analysis in this study using multiple regression analysis . Results of the multiple regression analysis of the data showed that the intensity of watching violence on television , emotion regulation , and secure attachment are jointly related to the tendency of juvenile delinquency with Fregresi value = 8.107 with a significance level of 0.000 ( p < 0.01 ) . Koefisisen regression watching violent intensity , emotion regulation , and secure attachment to the tendency of juvenile delinquency ( R ) = 0.426 , and the effective contribution of 18.2 % ( R Square = 0.182 ) . Furthermore , this study also found that more secure attachment contribute to the tendency of juvenile delinquency with a contribution of 11 percent , while the intensity of watching violence on television with a contribution of 3.5 percent , and emotion regulation with a contribution of 3.7 percent .